Oxford handbook of cardiac nursing (Oxford : Oxford University Press, 2021)
The Oxford Handbook of Cardiac Nursing is the indispensable companion for all those caring for cardiac patients. Fully revised and updated for the third edition and packed full of clinical information and practical advice, the book covers everything from assessment to cardiac rehabilitation. Each chapter has a list of pertinent evidence-based guidelines. This new edition contains the emergency treatment of stroke as well as a new section on genetics, and information on the management of valvular disease has been expanded.
Keywords: Cardiovascular diseases; Cardiovascular diseases; Cardiovascular diseases